Survey of tick-borne pathogens in grazing horses in Kyrgyzstan: phylogenetic analysis, genetic diversity, and prevalence of Theileria equi - Altay, Kursat; Erol, Ufuk; Sahin, Omer Faruk; Ulucesme, Mehmet Can; Aytmirzakizi, Ayperi; Aktas, Munir (Frontiers in Veterinary Science, 2024)
Tick-borne pathogens (TBP) are an important group of organisms that can affect animals and humans all over the world. Equine piroplasmosis (EP), caused by Theileria equi and Babesia caballi, is considered one of the most important tick-borne diseases and can cause significant clinical symptoms and mortality in horses. Moreover, EP plays a restrictive role in international horse traditions and transportation. Although these species can cause similar symptoms, there are different 18S rRNA genotypes of T. equi (five genotypes) and B. caballi (three genotypes).Besides piroplasma species, Anaplasma and hemotropic mycoplasmas (HM) are known as other important tick-borne pathogens reported in horses. In this study, we investigated the presence, prevalence, genetic diversity, and phylogenetic analyses of TBPs using PCRs and DNA sequencing in grazing horses in Kyrgyzstan. For these purposes, a total of 311 blood samples were collected from Chuy, Issyk-Kul, Naryn, Osh, Talas, and Jalal-Abad. DNA amplification of TBP revealed that 23 (7.40%) out of 311 samples were found to be positive for T. equi. However, B. caballi, HM, A. phagocytophilum, and A. capra were not detected in this study. The infection rate of T. equi was higher in males (8.11%) than in females (6.35%) (p=0.2880) and in those older than 5 years (9.02%) than in the 1-4 age group (6.35%) (p=0.1950). Phylogenetic analysis of 18S rRNA revealed that A and E genotypes of T. equi have circulated in grazing horses in Kyrgyzstan. Information about the genetic diversity of T. equi is important for understanding the population dynamics of the species and developing effective control strategies against this pathogen. This is the first molecular investigation of A. capra in horses in Kyrgyzstan. Although this pathogen has been detected in different hosts in Kyrgyzstan, it was not detected in this study. However, considering the wide host spectrum of A. capra, it is thought that more large-scale studies are needed to understand the effect of horses on the epidemiology of this pathogen.